Catfish Zone / Teodora Chela Tiyus ... [et. al] - Tiyus, teodora Chela; Lasah, Agness; Pau, Jaras; Jau, Christina; Balang, Jenifer Leku (2008)
After doing extensive research on the business opportunity available in Kota Samarahan District Council area, we decided to specify our business in providing services to the public. Our group has come out with a partnership business plan which provides the freshwater fish supplier, which is ikan keli. Our organization will be known as Catfish Zone Company. In order to establish this business plan, all four major aspects ofthe plan including administrative, operational, marketing and financial planning have to be taken into consideration. This is important for any establishment of a business plan because it can help to predict the viability ofthe business, to forecast success and also to propose strategies for marketing view. In administration plan, it helps to manage the overall business objectives and goals in order to accomplish the purposes of business plan. It also deals with the remuneration of staffs and their responsibilities in the organization. Besides that, the list of office equipments and administration budget are taken into consideration. In operational plan, it helps to determine the process of operations in the business and will be presented by a flow chart format. This stage is where the manager has to prepare the schedule of operations so that it will make the operations run smoothly in productions. All the materials, machines and equipment, and manpower have to be listed properly according to the reasonable amount. Therefore, a layout plan and budget need to be prepared altogether with the expenses incurred in the business. In marketing plan, the manager needs to meet the customer needs and demands by determining the target group of customers. Furthermore, she have to describe clearly the products or services which offered to the customers in order to estimate the market size and market share to be compared with the competitors in the same industry. Other functions of marketing manager are to plan the marketing strategies to attract customers for the services and to forecast sales profit for the company in the future.